Algae and Clay Water Additives Differentially Impact Survival and Microbial Community Structure in Sablefish (Anoplopoma fimbria) Rearing Tanks - Melissa L. Pierce; Jonathan S. F. Lee; Emily Dodd; Rachel S. Poretsky (Frontiers in Marine Science, 2019)

Dimethylsulfoniopropionate (DMSP) Increases Survival of Larval Sablefish, Anoplopoma fimbria - Jonathan S. F. Lee; Rachel S. Poretsky; Matthew A. Cook; Jose J. Reyes-Tomassini; Barry A. Berejikian; Frederick W. Goetz (Journal of Chemical Ecology, 2016)

Spatial patterns and light‐driven variation of microbial population gene expression in surface waters of the oligotrophic open ocean - Ian Hewson; Rachel S. Poretsky; H. James Tripp; Joseph P. Montoya; Jonathan P. Zehr (Environmental Microbiology, 2010)
Summary Because bacterioplankton production rates do not vary strongly across vast expanses of the ocean, it is unclear how variability in community structure corresponds with functional variability in the open ocean. We surveyed community transcript functional profiles at eight locations in the open ocean, in both the light and in the dark, using the genomic subsystems approach, to understand variability in gene expression patterns in surface waters. Metatranscriptomes from geographically distinct areas and collected during the day and night shared a large proportion of metabolic functional similarity (74%) at the finest metabolic resolution possible. The variability between metatranscriptomes could be explained by phylogenetic differences between libraries (Mantel test, P Prochlorocococcus marinus , where most geographical and diel variability between metatranscriptomes reflected between‐station differences in cyanobacterial phototrophic metabolism. Our results demonstrate that active genetic machinery in surface waters of the ocean is dominated by photosynthetic microorganisms and their site‐to‐site variability, while variability in the remainder of assemblages is dependent on local taxonomic composition.

Transporter genes expressed by coastal bacterioplankton in response to dissolved organic carbon - Rachel S. Poretsky; Shulei Sun; Xiaozhen Mou; Mary Ann Moran (Environmental Microbiology, 2010)
Summary Coastal ocean bacterioplankton control the flow of dissolved organic carbon (DOC) from terrestrial and oceanic sources into the marine food web, and regulate the release of inorganic carbon to atmospheric and offshore reservoirs. While the fate of the chemically complex coastal DOC reservoir has long been recognized as a critical feature of the global carbon budget, it has been problematic to identify both the compounds that serve as major conduits for carbon flux and the roles of individual bacterioplankton taxa in mediating that flux. Here we analyse random libraries of expressed genes from a coastal bacterial community to identify sequences representing DOC‐transporting proteins. Predicted substrates of expressed transporter genes indicated that carboxylic acids, compatible solutes, polyamines and lipids may be key components of the biologically labile DOC pool in coastal waters, in addition to canonical bacterial substrates such as amino acids, oligopeptides and carbohydrates. Half of the expressed DOC transporter sequences in this coastal ocean appeared to originate from just eight taxa: Roseobacter , SAR11, Flavobacteriales and five orders of γ‐ Proteobacteria . While all major taxa expressed transporter genes for some DOC components (e.g. amino acids), there were indications of specialization within the bacterioplankton community for others (e.g. carbohydrates, carboxylic acids and polyamines). Experimental manipulations of the natural DOC pool that increased the concentration of phytoplankton‐ or vascular plant‐derived compounds invoked a readily measured response in bacterial transporter gene expression. This highly resolved view of the potential for carbon flux into heterotrophic bacterioplankton cells identifies possible bioreactive components of the coastal DOC pool and highlights differing ecological roles in carbon turnover for the resident bacterial taxa.

Comparative day/night metatranscriptomic analysis of microbial communities in the North Pacific subtropical gyre - Rachel S. Poretsky; Ian Hewson; Shulei Sun; Andrew E. Allen; Jonathan P. Zehr; Mary Ann Moran (Environmental Microbiology, 2009)
Summary Metatranscriptomic analyses of microbial assemblages ( Cyanobacteria contributed a greater percentage of the transcripts (54% of annotated sequences) than expected based on abundance (35% of cell counts and 21% 16S rRNA of libraries), and may represent the most actively transcribing cells in this surface ocean community in both the day and night. Major heterotrophic taxa contributing to the community transcriptome included α ‐Proteobacteria (19% of annotated sequences, most of which were SAR11‐related) and γ ‐Proteobacteria (4%). The composition of transcript pools was consistent with models of prokaryotic gene expression, including operon‐based transcription patterns and an abundance of genes predicted to be highly expressed. Metabolic activities that are shared by many microbial taxa (e.g. glycolysis, citric acid cycle, amino acid biosynthesis and transcription and translation machinery) were well represented among the community transcripts. There was an overabundance of transcripts for photosynthesis, C1 metabolism and oxidative phosphorylation in the day compared with night, and evidence that energy acquisition is coordinated with solar radiation levels for both autotrophic and heterotrophic microbes. In contrast, housekeeping activities such as amino acid biosynthesis, membrane synthesis and repair, and vitamin biosynthesis were overrepresented in the night transcriptome. Direct sequencing of these environmental transcripts has provided detailed information on metabolic and biogeochemical responses of a microbial community to solar forcing.